2012
DOI: 10.1002/pssa.201228181
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐alloyed ZnS as a p‐type transparent conducting material

Abstract: A study of samarium powder‐catalyzed cross‐coupling reactions of aryl halides with terminal alkynes is described. The couplings performed in the polyethylene glycol PEG‐600 provided the corresponding coupling products in good yields. The first example of palladium‐free, copper‐free and amine‐free catalytic system for Sonogashira couplings is presented in the absence of ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 31 publications
1
54
1
Order By: Relevance
“…SI), it should function as an acceptor, producing free holes. [47,56] The connectivity of the hole-conducting phase is such that conductivity is independent of temperature. Conductivity increases with increasing Cu substitution until its maximum at x = 0.30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SI), it should function as an acceptor, producing free holes. [47,56] The connectivity of the hole-conducting phase is such that conductivity is independent of temperature. Conductivity increases with increasing Cu substitution until its maximum at x = 0.30.…”
Section: Discussionmentioning
confidence: 99%
“…The films exhibited p-type conductivity and optical transparency in the visible range. [47] Here we show that Cu x Zn 1-x S films can be synthesized at room temperature by pulsed laser deposition, and investigate the structure and conductivity mechanism in greater detail. At an optimal Cu concentration of x = 0.30, the hole conductivity reaches 42 S cm -1 and the material retains high optical transparency.…”
Section: Introductionmentioning
confidence: 87%
“…Up to now, various film preparation techniques have been successfully employed to produce Cu-doped ZnS thin films such as spray pyrolysis [19], electron beam evaporation [17], chemical bath deposition [20] by a pH controlled solution synthesis technique [15,21], pulsed laser deposition [18] and thermal reaction process [10] combined with dip coating. Among these film preparation techniques, the sol-gel (a wet chemical route) dip coating has become important in both scientific and industrial fields in only for the last two decades due to its several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several such materials have recently been synthesized and characterized. Cu-doped ZnS has also shown promising characteristics, as it was recently shown to exhibit the best reported hole conductivity and optical transparency for a room temperature-deposited p-type TCM 12,13 ; pairing this with n-doped ZnS may result in many promising device applications for photovoltaics, optoelectronics and transparent devices 14 . Traverse et al 2 enhanced the efficiency of thin film organic solar cells by introducing ZnS co-deposited with Al 2 S 3 ; they reported that the wide band gap hexagonal zinc sulfide (ZnS) (E g = 3.7 eV) can be a good alternative to conventional materials as the anodic buffer layer in OPVs and IGS-based PVs, as it can be thermally deposited in a vacuum environment.…”
mentioning
confidence: 99%